Legal certainty regarding pluralism of inheritance law in Indonesia in the transfer of inheritance rights in Indonesia - Suryawan, I Nengah Pasek; Sara, Rineke (Indonesian Journal of Multidisciplinary Science, 2024)
In Indonesia, the inheritance law system is divided into civil, Islamic, and customary law. In the context of inheritance rights transfer, the diversity of legal systems that include civil inheritance law, Islamic law, and inheritance law creates its own challenges that can trigger conflicts among heirs. This article discusses the legal certainty of pluralism in inheritance law in Indonesia from these three aspects, as well as the procedures for transferring rights to inheritance in accordance with the applicable legal system. The article aims to provide a comprehensive understanding of the complexities involved in the legal processes surrounding inheritance. The research emphasizes the need for legal certainty and clearer guidelines to protect heir's rights while advocating for strategies such as clear wills and mediation to mitigate conflicts. Furthermore, it offers practical policy recommendations aimed at harmonizing inheritance laws and fosters a more equitable legal environment that respects Indonesia's cultural diversity.